PENEGAKAN HUKUM OLEH KEPOLISIAN TERHADAP PELAKU PENANGKAPAN IKAN DENGAN MENGGUNAKAN PUKAT HARIMAU (TRAWL) DI WILAYAH BUNGUS TELUK KABUNG KOTA PADANG SUMATERA BARAT - Hartina, Dian; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Indonesia is one country that has at the same time two geographical forms of a countrycharacteristic, namely the archipelagic state and the mainland state. Indonesia is located between twocontinents, namely the Asian Continent and the Australian Continent, and two oceans, namely the AtlanticOcean and the vast Indian Ocean. Then automatically Indonesia also has a deep sea and the sea which isbetween the islands commonly called the strait. Indonesia which is in a position flanked by two oceans alsocauses the sea or waters in Indonesia to have a variety of abundant natural resources, one of which is alsovery abundant fish and various types. Law of the Republic of Indonesia Number 45 Year 2009 Amendment toLaw Number 31 Year 2004 concerning fisheries article 9 which regulates the prohibition on the use of trawl(Trawl Tiger) fishing gear and everything related to damaging fishing gear. And as one of the countriesthat initiated the recognition of countries with the principles of the archipelago in the United NationsConvention on The Law of the Sea (UNCLOS) 1982 Article 73 paragraph (4) became Law number 17 of1985 concerning Ratification of the United Nations Convention On The Law of the Sea (United NationsConvention on the Law of the Sea). With the 1982 United Nations Convention on the Law of the Sea(UNCLOS), it is not only Indonesia that benefits from the arrangements contained in its articles but also theinternational community in general. However, the sanction provisions contained in the law do not have adeterrent effect . The research method that the authors use is the field research method with research usingan empirical approach and the nature of descriptive research in order to analyze the sanction system in theFisheries Law using the theory of criminal acts and law enforcement. The approach used is a sociologicaljuridicalapproach, namely research conducted on real conditions in the environment of the Ministry ofMaritime Affairs and Fisheries (KKP) and local fishermen in the waters of the Bungus Bay area of Kabung,Padang, West Sumatra City. The result of this research concludes that the provisions of sanctions in theFisheries Law are in accordance with the sanction system in criminal law, which is a two-track system ordouble track system. However, at the level of implementation, the provisions of sanctions are not applied tothe maximum. In addition, the provisions of existing sanctions have not yet reached the goal of punishmentand legal objectives. Therefore it is necessary to adjust the sanctions system in the Fisheries Act with thesanctions system in criminal law, so that sanctions should be determined that should be applied to fisheriescriminal offenders.Keywords: Fishing Using Tiger Trawl (TRAWL) - Law Enforcement by the Police